Investigating Study on Future Port Perception - Hossain, K Akhter (Transactions on Engineering and Computing Sciences, 2025)
Ports plays a vital role of global economy by transporting 80% of trade and commerce of globe by value pass through them. The economic benefits are often less directly tied to port activities and more linked to the dynamics of the supporting supply chains. This operational support becomes beneficial and effective, playing a crucial role in enhancing national competitiveness. Smart ports are modern and highly facilitated port which uses digital, automated and other smart technologies to enhance efficiency, accountability, sustainability, competitiveness, monitoring, operations, and security. Smart ports frequently utilize digital tools such as sensors, data analytics, augmented reality, big data, digital twins, and automation to improve cargo movement, minimize waste and emissions, and provide superior services to shippers, shipping companies, customs authorities, local communities, and stakeholders. They may also feature renewable energy sources, electric charging stations, onshore power supply, sustainable to climate change, natural calamities, and smart infrastructure for better logistics and optimum transportation. This analytical paper will investigate the future development of port in contrast of history, global demand and advanced technology.